Assessment of antidiabetic activity (α-amylase, α-glucosidase and dipeptidyl peptidase-IV inhibitory activities) of collagen hydrolysate recovered from buffalo hide along with its characteristics and antioxidant properties - Veppalampatti Ramanathan Santhosh; Tanbir Ahmad; Prince Devadason Immanuel; Devendra Kumar; Suman Talukder; Ashim Kumar Biswas; Sanjod Kumar Mendiratta; Zunjar Baburao Dubal; Ajay Kumar; Yasotha Thirupathi; C. K. Faslu Rahman; Anand Thoppil Shaji; et al. (Food and Humanity, 2026)

Association of AGT and AGTR1 gene polymorphisms with chronic kidney disease: a case-control and in silico study - Farheen Khan; Saliha Rizvi; Syed Tasleem Raza; Devendra Kumar; Tanveer Ahamad (Molecular Biology Reports, 2026)

Co-evolution rhizosphere-microbe-mineral interfaces govern soil organic carbon stabilization and fertility - Sudhir Kumar Upadhyay; Antra Andotra; Prasann Kumar; Padmanabh Dwivedi; Devendra Jain (Applied Soil Ecology, 2026)

Sustained-release fertilizers for nutrient-use efficiency and environmental resilience: A critical and integrative review - Vivek Kumar Dhiman; Rakesh Kumar; Babit Kumar Thakur; Vinay Kumar Dhiman; Mukul Sharma; Prashant Sharma; Garima Rana; Ritesh Verma; Devendra Singh (Journal of Environmental Chemical Engineering, 2026)

Remote Sensing for Irrigation Water Management—The State of the Art and Prospects for Near‐Future Operations - Wim G. M. Bastiaanssen; Chris Perry; Royce Dalby; Yasir Mohamed; Xueliang Cai; Poolad Karimi; IJsbrand de Jong; Pasquale Steduto; Marat Beksultanov; Christopher C. M. Neale; David Molden; Waqas Awan; et al. (Irrigation and Drainage, 2026)
A recent UN report describes many regions as facing ‘water bankruptcy, ’ a condition in which available water resources can no longer meet existing demands. In practice, this means irrigation will likely bear the greatest burden of future water‐use reductions, a complicated and fraught decision to make given its critical role in food security. This review paper highlights the growing range of information now available through remote sensing technologies to support planners, irrigation managers and farmers. These data include cropping patterns, crop yields, water consumption, farmgate water and tubewell water deliveries, soil moisture and root‐zone water storage, among others. The paper also reviews current applications of remote sensing, which remain too often constrained to the scientific community, and recommends the development and dissemination of standardized irrigation analytics and diagnostic tools. Government irrigation and water agencies are encouraged to integrate these emerging spatial data sources into both strategic planning and real‐time management from field to scheme scale and provide a stronger foundation of key performance indicator (KPI). Bridging this information gap will require startups and technology providers to translate advanced data products into practical, user‐friendly tools tailored to the needs of the irrigation sector.

EDTA enabled chelation for stability and sensory quality in iron enriched coffee - Yashwanth Bevahalli Srinivasappa; Vijay Laxmi Biswal; Sachin Rama Chaudhari; Devendra Jagannath Haware; Sudheer Kumar Yannam; Pushpa Srinivas Murthy (Food Chemistry, 2026)

In vitro regeneration, genetic fidelity and phytochemical analysis of near threatened Ophiorrhiza mungos via meta-Topolin (mT) and melatonin (MEL) - Merinashwari Konjengbam; Tuyelee Das; Sudhir Kumar Upadhyay; Devendra Kumar Pandey (Journal of Plant Biochemistry and Biotechnology, 2026)

Harnessing omics and molecular breeding for developing drought-resilient rice varieties - Rouf Parray; Alok Kumar Singh; Devendra Pratap Singh; Zakir Amin; Bhagyashree Dulakakharia; Gracia Priya Kumari; Bushra Rasool; Debashish Panda; Nabarun Roy; Sajad Un Nabi; Akhil Baruah; Tabia Fayaz; et al. (Cereal Research Communications, 2026)

Multitrait validation of submergence tolerance in rice through biochemical traits and microsatellite marker analysis - Alok Kumar Singh; Devendra Kumar Dwivedi; Ranjith Kumar Ellur; Chandan Kumar Singh; Rouf Parray; Amit Kumar Singh; Donato Gemmati; Veronica Tisato; Namuna Paudel; Nawaz Ahmad Khan; Rakesh Singh; Gyanendra Pratap Singh (Cereal Research Communications, 2026)

Revisiting plant–microbe interaction mechanisms for developing efficient biostimulants - Payal Chakraborty; Bandana Bose; Deepika Sharma; Devendra Kumar Choudhary (Folia Microbiologica, 2026)

Canine demodicosis: Associated factors, diagnostic approaches, and therapeutic evaluation - Supnesh Jain; Ranbir Singh Jatav; Rupesh Verma; Amita Tiwari; Rakesh Dangi; Aditya Pratap; Salil Kumar Pathak; Devendra Kumar Gupta (International Journal of Tropical Insect Science, 2026)

Application of Explainable AI-Driven Ensemble Modelling Approach for Robust Potato Disease Identification under Field Conditions - Kajal Verma; Mithilesh Kumar Dubey; Devendra Kumar Pandey (Potato Research, 2026)

Microbial-Molecular Synergy for Enhancing Centelloside Biosynthesis in Centella asiatica Integrating Genetic Regulation and Sustainable Elicitation - Shruti Singh; Devendra Kumar Pandey; Sudhir Kumar Upadhyay (Journal of Plant Growth Regulation, 2026)

In silico anticancer, antioxidant and anti-inflammatory study on GC–MS-based profiling of chloroform and hexane extracts of Erigeron multiradiatus - Devendra Singh Dhami; Charu Chandra Pant; Ritul Kumar; Pritee Pant (In Silico Pharmacology, 2026)

Soil microorganisms in the age of plastic pollution: effects of micro- and nano-plastics on soil health - Devendra Kumar; Archana T. S.; Richard Singh Hijam; Pranay; Vipul Kumar (Environmental Science and Pollution Research, 2026)

Comparative Effects of Organic and Conventional Farming Systems with Diversified Crop Rotations on Soil Microbial Dynamics and Productivity Under Arid Conditions - Devendra Singh; Mahipal Choudhary; Arun Kumar Sharma; Pramendra (Journal of Soil Science and Plant Nutrition, 2026)

Yellow slime mould (Physarum sp.) associated with poor quality basidiocarps in Auricularia cornea - Harvinder Kumar Singh; Pradeep Kumar Badhai; Devendra Kumar Choudhary; Shweta Singh; Chandramani Raj (Indian Phytopathology, 2026)

Genetic diversity of common bean cultivar mixtures enhance nutritional, agronomic, and sensory traits in low-input hill farming systems - Shree Prasad Neupane; Dipendra Kumar Ayer; Bal Krishna Joshi; Devendra Gauchan; Stefania Grando; Salvatore Ceccarelli (Euphytica, 2026)

Comprehensive phytochemical profiling, antibacterial, antioxidant, and in-silico evaluation of Aster thomsonii C.B. Clarke essential oil from the Kumaun Himalaya Region, Uttarakhand - Asha; Sandeep Kumar; Mukesh Samant; Charu Chandra Pant; Pritee Pant; Aashish Kumar Sagar; Devendra Singh Dhami (Natural Product Research, 2026)

Optimisation and comparative extraction of safranal from Crocus sativus L. stigmas and commercial saffron products using response surface methodology (RSM) and adaptive neuro-fuzzy inference system (ANFIS) - Devendra Kumar Pandey; Tuyelee Das; Babita Pandey (Natural Product Research, 2026)

Pesticide and metabolite residue mixtures in subtropical agroecosystem soils: The inconvenient truth - Shailendra Singh Shah; Vera Silva; Jos van Dam; Awtar Singh; Rima Osman; Devendra Singh Bundela; J. Bastiaan Mohrmann; Rajender Kumar Yadav; Violette Geissen; Coen J. Ritsema (Journal of Hazardous Materials, 2026)

Comparative diversity analysis of Valeriana jatamansi from different areas of Himachal Pradesh, India: A molecular and phytochemical approach - Ankita Sharma; Fariha Chowdhary; Suphla Gupta; Devendra Kumar Pandey (Biochemical Systematics and Ecology, 2026)

Unveiling nitric oxide-mediated defense mechanisms in wheat and rice seedlings against copper-oxide nanoparticle-induced growth inhibition with NG-nitro-L-arginine methyl ester: a comparative study - Namira Arif; Vaishali Yadav; Anuradha Patel; Imtiyaz Hussain; Charu Kalra; Vandana Sharma; Devendra Kumar Chauhan (Plant Biosystems, 2026)

Aquaporin gene expression and antioxidant responses in sugarcane genotypes under water deficit during formative growth stage - Devendra Kumar; Nisha Malik; Alok Kumar Singh; Rakesh Singh Sengar (Vegetos, 2026)

New addition of a scarcely distributed leafy liverwort- Bazzania wallichiana (Lindenb.) Trevis. to Indian bryoflora - Shashi Kumar; Meghna Paul; Devendra Singh (Vegetos, 2026)

Optimisation of heat reflux extraction of gallic acid, quercetin and chlorogenic acid from Stevia rebaudiana (Bertoni) leaves by using response surface methodology and adaptive neuro-fuzzy inference system modelling - Devendra Kumar Pandey; Tuyelee Das (Natural Product Research, 2026)

Understanding farmers' protective behavior towards pesticide use in Northern India: A health belief model approach using PLS-SEM and fsQCA - Shailendra Singh Shah; Jos van Dam; Liangxin Fan; Suresh Kumar; Awtar Singh; Devendra Singh Bundela; Rajender Kumar Yadav; J. Bastiaan Mohrmann; Violette Geissen; Coen J. Ritsema (Environmental Impact Assessment Review, 2026)

Efficient electron confinement and enhanced plasmonic support of Pt nanoparticles to AuNPs-SnO2 heterojunction for highly selective artificial photosynthesis - Dinesh Kumar; Richa Jaswal; Jeevitha Muniswamy; P. Muthu Austeria; Devendra Shrestha; Chan Hee Park (Chemical Engineering Journal, 2026)

Multi-Objective Variance-Bias Tradeoff Optimization of ANN by Hybridizing with Multi-Objective GA for Water Discharge Estimation - Arvind Yadav; Ashwini Kumar Pradhan; Manish Kumar; Priyaranjan Sharma; Sunil Kr. Maakar; Shivangi Singh; Umamaheswararao Batta; Devendra Joshi (Water Resources Management, 2026)

Genome-wide association studies revealed genomic regions associated with production and reproduction traits in indicine cattle - Javid Ur Rahman; Devendra Kumar; Satya Pal Singh; Bijendra Narayan Shahi; Ashis Kumar Ghosh; Tarannum Jahan (The Nucleus, 2026)

Landslide susceptibility mapping and kinematic analysis in Bachchangad catchment, Uttarakhand, India: a comparative study using machine learning benchmark classifiers - Khyati Gupta; Aasif Ibni Ahad; Devendra Singh Rawat; Syed Kaiser Bukhari; Bikash Kumar Ram; Govind Singh Rawat; Vikas Yadav; Ashutosh Kainthola; Tariq Siddique; Mohammad Azarafza (Natural Hazards, 2026)

Optimal placement of wildlife crossing structures along roads in an open natural ecosystem - Ashish Kumar Jangid; Devendra Dutta Pandey; Ashish Vyas; Malvika Onial; Sutirtha Dutta (Biodiversity and Conservation, 2026)

Determining Drought- and Heat-Tolerant Genotypes in Indian Mustard [Brassica juncea] Employing GGE Biplot Analysis - Yashpal Taak; Manoj Kumar Patel; Rajat Chaudhary; Sudhakar Reddy Basu; Priya Pardeshi; Sneha Adhikari; Joghee Nanjundan; Navinder Saini; Sujata Vasudev; Devendra Kumar Yadava (Agricultural Research, 2026)

Quantitative Proteomic Analysis of Serum-Derived Exosomes from Patients with and Without Human Immunodeficiency Virus–Tuberculosis Coinfection - Shweta Kushwaha; Rajbala Yadav; Roopendra Kumar; Anjana Goel; Santosh Kumar; Devendra Singh Chauhan; Ajay Vir Singh (Indian Journal of Clinical Biochemistry, 2026)

A comprehensive review on taxonomy, traditional uses, phytochemistry, pharmacological activities and quality control of Myrica esculenta - Amit Ranjan Pandey; Sunil Kumar; Rishi Ranjan Pandey; Devendra Pratap Mishra (Next Research, 2026)

Development and validation of mitochondrial citrate synthase enzyme-based sandwich ELISA for reliable authentication of fresh vs frozen thawed pork meat - T.S. Anand; Ashim Kumar Biswas; Sanchay Kumar Biswas; Ravi Kant Agrawal; Praveen Singh; Suman Talukder; Himani Dhanze; J.J. Rokade; C.K. Faslu Rahman; Bedika Bora; Namrata Agrawal; Tanbir Ahmad; et al. (Food Control, 2026)

Global expansion of lumpy skin disease: transmission trends, economic consequences, and preventive measures - Pragya Sharma; Devendra Kumar (Veterinary Research Communications, 2026)

Unlocking the genetic and molecular secrets of thousand-seed weight in Indian mustard [Brassica juncea (L.) Czern. & Coss.] employing generation mean and candidate gene analysis - Manoj Kumar Patel; Masochon Zimik; Sneha Adhikari; Yashpal Taak; Navin C. Gupta; Joghee Nanjundan; K. K. Vinod; Sujata Vasudev; Devendra Kumar Yadava; Navinder Saini (Planta, 2026)

Enhanced tannery wastewater remediation using a synergistic Bacillus licheniformis and Auxenochlorella pyrenoidosa consortium - Anuradha Devi; Devendra Kumar Patel; Gubbala Naga Venkata Satyanarayana; Vartika Jain; Ganesh Dattatraya Saratale; Luiz Fernando R. Ferreira; Ram Naresh Bharagava (Environmental Sustainability, 2026)

Conservation agriculture for riverine agri-food systems under the climate crisis: enhancing soil health and mitigating erosion - Pazhanisamy S.; Devendra Singh; Rodda Chandana Devi; Vijay Singh Meena; Sunil Kumar; R.S. Singh; S.S. Prasad; R. Sushma Devi; Jogdande Sai Prasad; K. Damodar; Abhinandan Singh; V. Sridevi; et al. (Soil and Tillage Research, 2026)

Understanding the mechanistic insight and relevance of root hair-driven rhizobia for developing climate-smart crops - Sudhir Kumar Upadhyay; Prasann Kumar; Devendra Jain (Plant Science, 2026)

A critical review on agarwood: biosynthesis, therapeutic potential, trade, and conservation challenges - Acharya Balkrishna; Vijay Kumar; Devendra Kumar; Deepika Arya; Vedpriya Arya; Ajay Kumar Gautam (Next Research, 2026)

Utilization of Genetically Engineered RuBisCO Enzyme for Capturing Carbon Dioxide to Address Environmental Challenges-An Overview - Priya Gupta; Rajkumar Prabhakaran; Nalini Soni; Sangeeta Devendra Kumar Singh; Chinnaperumal Kamaraj; Silambarasan Tamil Selvan; Neethu Asokan; Sudheer D. V. N. Pamidimarri; Balasubramanian Velramar (Water, Air, & Soil Pollution, 2026)

Pretomanid for the treatment of drug resistant pulmonary tuberculosis: a comprehensive review - Roopendra Kumar; Jagdeep Singh Sohal; Ajay Vir Singh; Devendra Singh Chauhan (Archives of Microbiology, 2026)

Microbial mechanisms targeting mineralization-mobilization dynamics and balance in rhizosphere: A necessity for future rhizosphere-soil health - Sudhir Kumar Upadhyay; Prasann Kumar; Devendra Jain; Yogesh K. Ahlawat; Xiuyun Zhao (Rhizosphere, 2025)

Harnessing microbial consortia to induce systemic resistance and modulate gene expression in cluster bean under bacterial blight (Xanthomonas axonopodis pv. cyamopsidis) stress - Devendra Singh; Hans Raj Mahla; Rajesh Kumar Kakani (World Journal of Microbiology and Biotechnology, 2025)

Recent advances in phosphorus nano-fertilizers: Impacts on crop productivity and soil sustainability - Vivek Kumar Dhiman; Vinay Kumar Dhiman; Garima Rana; Rakesh Kumar; Devendra Singh; Ankush Chauhan; Majid Jabir; Suresh Ghotekar (Physiological and Molecular Plant Pathology, 2025)

meta-Topolin as an effective cytokinin for high-frequency regeneration and clonal fidelity in Capsicum chinense Jacq. cv. Naga Chili - Aditi Sharma; Devendra Kumar Pandey (The Nucleus, 2025)

Impact of subsurface drainage on soil solution chemistry, structural stability and clay mineralogy of waterlogged saline soils - Raj MUKHOPADHYAY; Diksha SAROHA; Ranjan PAUL; Bhaskar NARJARY; Devendra S. BUNDELA; Satyendra KUMAR; Binoy SARKAR (Pedosphere, 2025)

Convergence of nanotechnology and microbial-electrochemical systems for next-generation of toxic heavy metal and organic pollutant soil removal - Sudhir Kumar Upadhyay; Prasann Kumar; Devendra Jain; Xiuyun Zhao (Journal of Environmental Chemical Engineering, 2025)

Accelerated development of MTL and DMP gene-based subtropically-adapted maternal haploid inducer lines in maize using molecular breeding - Nisrita Gain; Vignesh Muthusamy; Rashmi Chhabra; Amitkumar D. Kyada; Suman Dutta; Gulab Chand; Ravindra K. Kasana; Konsam Sarika; Elangbam L. Devi; Jayanthi Madhavan; Rajkumar Subramani; Rajkumar U. Zunjare; et al. (Planta, 2025)

Pre-breeding to molecular breeding for crop improvement of Spine gourd (Momordica dioica Roxb.): challenges and opportunities - Suchismita Chatterjee; Preeti Sagar; Anjali Singh; Anjali Sharma; Yogendra Kumar Mishra; Devendra Upadhyay; Jitendra Kumar Tiwari; Anil Kumar (Euphytica, 2025)

Application of Different Transfer Learning Models to Classify Destructive Insects in Walnut Fruit - Khalil Ahmed; Mithilesh Kumar Dubey; Devendra Kumar Pandey (Applied Fruit Science, 2025)

Pedicularis dhurensis R.R. Mill (Orobanchaceae), a new record for India from Arunachal Pradesh - Madhusudhan Khanal; Bishal Kumar Majhi; Shuvadip Sarkar; Kingsuk Sarkar; Santosh Kumar Rai; Devendra Kumar; Arti Garg (Vegetos, 2025)

Combined challenges posed by climate change and pollution to river ecosystems: exploring connecting links, hydro-biological impacts and future research approaches - Ashutosh Tripathi-II; Sarojni Rai; Devendra Kumar Soni; Ashutosh Tripathi-I; Poonam Pandey (Environmental Sustainability, 2025)

Nanomaterials for sustainable agriculture: Plant physiology and environmental resilience - Vivek Kumar Dhiman; Garima Rana; Vinay Kumar Dhiman; Rajasekaran Subbarayan; Mukul Sharma; Devendra Singh; Majid Jabir; Suresh Ghotekar; Ankush Chauhan (Physiological and Molecular Plant Pathology, 2025)

Fabrication and in vitro evaluation of Dox@FeSe Nanorods for independent photothermal and chemotherapeutic effects toward theranostic cancer treatment - Purnima Justa; Nancy Jaswal; Devendra Kumar Gangwar; Dimple Kumari; Pramod Kumar (Next Research, 2025)

Life cycle responses of earthworm, Eisenia fetida to soil contaminated with crude oil sludge containing polycyclic aromatic hydrocarbons (PAHs) - Salil Srivastava; Krishna Gautam; Ved Prakash; Varsha Tripathi; Ravindra Singh Thakur; Devendra Kumar Patel; Dhirendra Singh; Sadasivam Anbumani; Natesan Manickam (Environmental Pollution, 2025)

Retraction Note: Role of Polyamines in Molecular Regulation and Cross-Talks Against Drought Tolerance in Plants - Samapika Nandy; Saynati Mandal; Santosh Kumar Gupta; Uttpal Anand; Mimosa Ghorai; Avinash Mundhra; Md. Habibur Rahman; Puja Ray; Sicon Mitra; Durga Ray; Milan Kumar Lal; Rahul Kumar Tiwari; et al. (Journal of Plant Growth Regulation, 2025)

Variability of Bipolaris maydis in relation to maydis blight severity in maize - Devendra Kumar; Santosh Kumar Singh; Seethiya Mahajan; Rafakat Hussain; T. S. Archana (Indian Phytopathology, 2025)

Unveiling the research trends and visualization of vector borne plant virus diseases through bibliometric analysis - Pritha Ghosh; T. S. Archana; Devendra Kumar (Vegetos, 2025)

Toxicity and risk assessment of landfill leachate on the earthworm, Eisenia fetida - Krishna Gautam; Namrata Pandey; Anshul Tiwari; Devendra Kumar Patel; Andy Turner; Awadhesh N. Jha; Sadasivam Anbumani (Science of The Total Environment, 2025)

Coupling of downscaled GRACE data with SPHY derived hydrological components to generate snow water equivalent in the Himalayan catchment - Vishal Singh; Devendra Shashikant Nagale; Japjeet Singh; Sanjay Kumar Jain; A.P. Dimri (Advances in Space Research, 2025)

Pinus radiata forest residue: A bio-adsorbent of choice for Cr (VI) removal from aqueous solution - Humberto Dax Bonilla Mancilla; Jenny Del Pino Moreyra; Juan José Bullon Rosas; Alfredo Rubén Bernal Marcelo; Candelaria Tejada Tovar; Manoj Kumar Jindal; Devendra Kumar; Mika Sillanpää; Djamel Ghernaout (Environmental Nanotechnology, Monitoring & Management, 2025)

Nanotechnology in agriculture: enhancing crop productivity and addressing toxicity in plants and algae - Sanjesh Tiwari; Anuradha Patel; Vaishali Yadav; Arushi Khandelwal; Rajat P. Singh; Devendra Arya; Satyam Lavaniya; Namrita Meena; Akhilesh Kumar; Neeraj Pandey; Sheo Mohan Prasad (Nanotechnology for Environmental Engineering, 2025)

Do traditional agri-silvicultural systems benefit farmers? A revelation by benefit–to-cost analysis of Grewia optiva on pea fields of Chakrata tehsil of Uttarakhand, India - Tara Kumari; Sohom Seal; Raman Nautiyal; Devendra Kumar (Agroforestry Systems, 2025)

Genetic resources for enhancing drought tolerance from National Genebank collection of linseed (Linum usitatissimum L.) in India - Vikender Kaur; Devendra K. Payasi; Rakesh Choudhary; Vishnu Kumar; Shashank K. Yadav; Devender Singh; Vinay Kumar; Balram Jat; Deepa Garg; Vishal Kumar Gupta; Sudhir Kumar; Viswanathan Chinnusamy; et al. (Plant and Soil, 2025)

Influence of pruning intensity on growth, yield and bio-chemical parameters of guava (Psidium guajava L.) Cv. Shweta under North Indian conditions - Vibhu Pandey; Arvind Kumar; Khushboo Sharma; Deepesh Keshari; Amit Kumar; Devendra Pal (Vegetos, 2025)

Coordination engineering of transition metal doped in B2CN3 electrocatalyst to enhance efficient carbon dioxide reduction reaction - Waqed H. Hassan; Anjan Kumar; G.V. Siva Prasad; Bhanu Juneja; Muna Salih Merza; Abdulrahman A. Almehizia; Devendra Pratap Rao; Chou-Yi Hsu (Sustainable Chemistry and Pharmacy, 2025)

High-performance nitrogen-polymer fertilizer: Synthesis, characterization, and application in sustainable agriculture - Rudramani Tiwari; Jarupula Suman; Dipendra Kumar Verma; Devendra Kumar; Shashikant Yadav; Km Parwati; Rajshree Rai; Shailja Rai; Krishna Kumar; S. Krishnamoorthi; Amitava Rakshit (Chemical Engineering Journal, 2025)

Molecular Mechanistic of Zn-Solubilizing Bacteria for Agronomic Eminence: Recent Updates and Futuristic Development - Nitu Rani; Arjun Chauhan; Sukhminderjit Kaur; Manoj Kumar Solanki; Manikant Tripathi; Devendra Jain; Shraddha Singh; Sudhir K. Upadhyay; Gurparteek Kaur (Journal of Plant Growth Regulation, 2025)

Physiological characterization of bael genotypes of sub-tropical region of India for cold hardiness and fruit quality - Shiv Poojan; Sharad Kumar Dwivedi; Devendra Pandey; Sanjay Kumar Singh; Saba Siddiqui; Himanshu Pandey; Jagveer Singh; Kuldeep Pandey; Rajni Rajan (Genetic Resources and Crop Evolution, 2025)

Harnessing nature’s defenders: unveiling the potential of microbial consortia for plant defense induction against Alternaria blight in cumin - Devendra Singh; Kuldeep Singh Jadon; Aman Verma; Rajesh Kumar Kakani (Folia Microbiologica, 2025)

Corrigendum to “Assessment of potentially toxic elements in some wild edible plants of district Doda, Jammu and Kashmir, India” [J. Geochem. Explor. 267, p. 107604. (Dec 2024)] - Sania Hamid; Devendra Kumar Pandey; Deepika Singh (Journal of Geochemical Exploration, 2025)

Application of quality by design in optimization of nanoformulations: Principle, perspectives and practices - Devendra Birla; Nikhil Khandale; Bushra Bashir; Md. ShahbazAlam; Sukriti Vishwas; Gaurav Gupta; Harish Dureja; Popat S. Kumbhar; John Disouza; Vandana Patravale; Francisco Veiga; Ana Cláudia Paiva-Santos; et al. (Drug Delivery and Translational Research, 2025)

Development of sheath blight resistant genotype of rice by mutation breeding and gene expression profiling after inoculation of Rhizoctonia solani - Reeshu Singh; Devendra Kumar Dwivedi; Anurag Mishra; Ashutosh Singh (Cereal Research Communications, 2025)

Chitosan nanoparticles of imatinib mesylate coated with TPGS for the treatment of colon cancer: In-vivo & in-vitro studies - Darshan Bhirud; Sankha Bhattacharya; Harshvardhan Raval; Preeti Chidambar Sangave; Girdhari Lal Gupta; Gaurav Paraskar; Megha Jha; Satyam Sharma; Sateesh Belemkar; Devendra Kumar; Rahul Maheshwari; Mayank Sharma (Carbohydrate Polymers, 2025)

Genome-wide association studies of milk composition traits in indicine Badri cattle using ddRAD sequencing approach - Javid Ur Rahman; Devendra Kumar; Satya Pal Singh; Bijendra Narayan Shahi; Ashis Kumar Ghosh; Aashaq Hussain Dar; Oshin Togla (Tropical Animal Health and Production, 2025)

Forest structure and tree diversity along an altitudinal gradient in Sikkim Himalaya - Mamta Chettri; Uttam Kumar Sahoo; Devendra Kumar; Faisal Ismail Musa; Ahmed Abdallah Adam Mohamed; Lalrempuii Hrahsel; P. C. Vanlalhluna (Vegetos, 2024)

Impact of irrigation, fertilizer, and pesticide management practices on groundwater and soil health in the rice–wheat cropping system—a comparison of conventional, resource conservation technologies and conservation agriculture - Shailendra Singh Shah; Jos van Dam; Awtar Singh; Suresh Kumar; Satyendra Kumar; Devendra Singh Bundela; Coen Ritsema (Environmental Science and Pollution Research, 2024)

Toxicity assessment of wastewater treatment plant sludge using Caenorhabditis elegans - Mrityunjay C Chinkate; Anshul Tiwari; Devendra Kumar Patel; Aruna Satish (Journal of Biosciences, 2024)

Retraction notice: In vitro propagation and assessment of genetic fidelity in Dioscorea deltoidea, a potent diosgenin yielding endangered plant - Romaan Nazir; Suphla Gupta; Abhijit Dey; Vijay Kumar; Muzamil Yousuf; Shahnawaz Hussain; Padmanabh Dwivedi; Devendra Kumar Pandey (South African Journal of Botany, 2024)

Assessment of potentially toxic elements in some wild edible plants of district Doda, Jammu and Kashmir, India - Sania Hamid; Devendra Kumar Pandey; Deepika Singh (Journal of Geochemical Exploration, 2024)

Assessing the drought-tolerance and growth-promoting potential of strawberry (Fragaria × ananassa Duch.) rhizobacteria for consortium bioformulation - Vinay Kumar Dhiman; Neerja Rana; Sudarshna; Vivek Kumar Dhiman; Prashant Sharma; Devendra Singh (Ecological Genetics and Genomics, 2024)

Retraction notice to “Evaluation of hydrotropic pretreatment on lignocellulosic biomass” [Bioresour. Technol. 213 (2016) 350–358] - Leena P. Devendra; M. Kiran Kumar; Ashok Pandey (Bioresource Technology, 2024)

Eco-friendly Synthesis of Cu11O2(VO4)6 Nanoparticles via Linum usitatissimum for Photocatalytic Degradation of Rose Bengal Dye and Photoluminescence Studies - Adheena Biju; Soundarya T.L; Naveen Kumar J.R; Bharath K. Devendra; Prabhu; Praveen B.M; Nagaraju G (Water Conservation Science and Engineering, 2024)

Antioxidant machinery modulation by phosphorus mitigates zinc oxide nanoparticle toxicity in Triticum aestivum and Solanum lycopersicum seedlings - Vaishali Yadav; Namira Arif; Imtiyaz Hussain; Anuradha Patel; Sanjesh Tiwari; Devendra Kumar Chauhan; Sheo Mohan Prasad (Nanotechnology for Environmental Engineering, 2024)

Prevalence of rifampicin and isoniazid mono-resistance among cases of pulmonary tuberculosis from Western Uttar Pradesh, North India - Roopendra Kumar; Jagdeep Singh Sohal; Ajay Vir Singh; Devendra Singh Chauhan (Molecular Biology Reports, 2024)

Descriptors for characterization and evaluation of bael (Aegle marmelos (L.) Correa ex Roxb.) germplasm for utilization in crop improvement - A. K. Singh; Devendra Pandey; Raj Kumar; V. Yadav; L. P. Yadav; K. Gangadhara; Jagdish Rane; Rajeev Kumar; Hare Krishna (Genetic Resources and Crop Evolution, 2024)

Integration of SPEI and machine learning for assessing the characteristics of drought in the middle ganga plain, an agro-climatic region of India - Barnali Kundu; Narendra Kumar Rana; Sonali Kundu; Devendra Soren (Environmental Science and Pollution Research, 2024)

Policy dimension for promoting inter and intra-varietal diversity and evolutionary crop populations - Bal Krishna Joshi; Shree Prasad Neupane; Devendra Gauchan; Ajaya Karkee; Dipendra Kumar Ayer; Dejene Kassahun Mengistu (Euphytica, 2024)

Enhanced steroidal alkaloids accumulation under abiotic elicitation of in vitro cultures of Fritillaria roylei using response surface methodology - Mamta Gochar; Pooja Goyal; Kajal Katoch; Muzamil Wani; Ajai P. Gupta; Devendra Kumar Pandey; Javaid F. Lone; Sumeet Gairola; Suphla Gupta (In Vitro Cellular & Developmental Biology - Plant, 2024)

Design of solar cooking models to enhance energy utilization and environment protection with their cost–benefit analysis: a case study of an institutional area in the state of Rajasthan, India - Sujeet Kumar; Devendra Kumar Doda; Vijay Kumar Pandey (Environmental Science and Pollution Research, 2024)

Bioluminescent fungi: a flame of curiosity - Devendra Kumar; T. S. Archana; Jinat Rehena; Krishanu Ghosh; Sudipta Nandi; Debosmita Roy; Kashish Gupta (Indian Phytopathology, 2024)

Plant pathogen detection: exploring modern techniques and future directions - T. S. Archana; Devendra Kumar; Pritha Ghosh; Vipul Kumar (Indian Phytopathology, 2024)

Waste to wealth: microbial-based valorization of grape pomace for nutraceutical, cosmetic, and therapeutic applications to promote circular economy - Gurleen Kaur Sodhi; Gursharan Kaur; Nancy George; Harleen Kaur Walia; Devendra Sillu; Santosh Kumar Rath; Sanjai Saxena; Leonardo Rios-Solis; Vagish Dwibedi (Process Safety and Environmental Protection, 2024)

Natural dye-based sensor for monitoring temperature variation in storage for chicken patties - Suman Talukder; Sanjod Kumar Mendiratta; Ashim Kumar Biswas; Arup Ratan Sen; Immanuel Prince Devadason; Sagar Chand; Tanbir Ahmad; Devendra Kumar; Ravikant Agrawal; Ayon Tarafdar (Food Bioscience, 2024)

Comparative study of phytochemicals and pharmacological properties of different parts of Berberis sikkimensis (C. K. Schneid.) Ahrendt - Dheeraj Shootha; Deepika Tripathi; Mithilesh Singh; Purnima Rawat; Priyanka Srivastava; Devendra Kumar (Biochemical Systematics and Ecology, 2024)

Unveiling critical structural features for effective HDAC8 inhibition: a comprehensive study using quantitative read-across structure–activity relationship (q-RASAR) and pharmacophore modeling - Samima Khatun; Indrasis Dasgupta; Rakibul Islam; Sk. Abdul Amin; Tarun Jha; Devendra Kumar Dhaked; Shovanlal Gayen (Molecular Diversity, 2024)

Spatio-temporal distribution and source contributions of the ambient pollutants in Lucknow city, India - Priya Saxena; Ankit Kumar; Mohd. Muzammil; Sreekanth Bojjagani; Devendra Kumar Patel; Alka Kumari; Altaf Husain Khan; Ganesh Chandra Kisku (Environmental Monitoring and Assessment, 2024)

Performance analysis of a Savonius hydrokinetic turbine with aerodynamic blade shape and different overlap ratios: A numerical flow-driven approach - Gudlavalleti Vamsi Babu; Devendra Kumar Patel (Ocean Engineering, 2024)

Deferoxamine Ameliorates Cypermethrin-Induced Iron Accumulation and Associated Alterations - Nidhi Sachan; Saripella Srikrishna; Devendra Kumar Patel; Mahendra Pratap Singh (Molecular Neurobiology, 2024)

HPTLC quantification of quercetin from leaf extracts of C. occidentalis L. and its inhibitory activity against protease enzyme of P. falciparum - Ibrahim Isyaku Muhammad; Devendra Kumar Pandey (Vegetos, 2024)

Architecture dependent transport behavior of iron (0) entrapped biodegradable polymeric particles for groundwater remediation - Kalpana Pandey; Devendra Kumar Verma; Awaneesh Singh; Sampa Saha (Chemosphere, 2024)

Development of superoxide dismutase based visual and spectrophotometric method for rapid differentiation of fresh and frozen-thawed buffalo meat - Apeksha Jangir; Ashim Kumar Biswas; Abdullah Arsalan; C.K. Faslu Rahman; Shalu Swami; Ravikant Agrawal; Bedika Bora; Sanjod Kumar Mendiratta; Suman Talukder; Sagar Chand; Devendra Kumar; Tanbir Ahmad; et al. (Food Chemistry, 2024)

Genetic relatedness analysis in sapota using SSR markers - Hemangini Rathva; Avnish Kumar Pandey; Kiran Suthar; Harish Suthar; Ankita Chakote; Diwakar Singh; Timur Ahlawat; Vinay Parmar; Vivek Kumar Dhiman; Himanshu Pandey; Devendra Singh (Ecological Genetics and Genomics, 2024)

Arbuscular mycorrhizal fungi promote growth and enhance the accumulation of bioactive compounds in Tomato (Solanum lycopersicum L.) - Meenakshi Singh; Ambika Chauhan; Devendra Kumar Srivastava; Pradeep Kumar Singh (Biologia Futura, 2024)

Exploring the association between long-term MODIS aerosol and air pollutants data across the Northern Great Plains through machine learning analysis - Neeraj Kumar Singh; Pradeep Kumar Verma; Arun Lal Srivastav; Sheo Prasad Shukla; Devendra Mohan; Markandeya (Science of The Total Environment, 2024)

Exploring rice straw’s potential from a sustainable biorefinery standpoint: Towards valorization and diverse product production - Saumya Singh; Gurkanwal Kaur; Devendra P. Singh; Shailendra Kumar Arya; Meena Krishania (Process Safety and Environmental Protection, 2024)

Enabling industry 4.0: Assessing technologies and prioritization framework for agile manufacturing in India - Devendra Kumar Prajapati; K. Mathiyazhagan; Vernika Agarwal; Vijaya Sunder M; Sangeeta Khorana; Angappa Gunasekaran (Journal of Cleaner Production, 2024)

An assessment of pearl millet hybrids for drought tolerance under hyper arid conditions - Mamta; Vishnu Prakash Agarwal; Ravindra Kumar; Devendra Chandel; Sunita Gupta; Narendra Kumar Gupta; Yemmanur Sudarsan (Vegetos, 2024)

Potential health risks assessment associated with arsenic-contaminated groundwater in the eastern district of Uttar Pradesh, India: a case study - Devendra Kumar Soni; Pradeep Kumar Mishra; Poonam Pandey (Environmental Sustainability, 2024)

Effect of various chemical solutions on micropropagation efficiency, antioxidant activities and clonal fidelity analysis of in vitro developed plantlets in pomegranate (Punica granatum L.) using SSR markers - Devendra Pal; Mukesh Kumar; Manoj Kumar Yadav; Chetan Chauhan; Arvind Kumar; Ujjwal Sirohi; V. Rakesh Sharma; Veena Chaudhary (Vegetos, 2024)

Putative Role of Anti-microbial Peptide Recovered from Lactiplantibacillus spp. in Biocontrol Activity - Ishan Tiwari; Ali Asger Bhojiya; Ram Prasad; Shalini Porwal; Ajit Varma; Devendra Kumar Choudhary (Current Microbiology, 2024)

Prospecting the Potential of Plant Growth-Promoting Microorganisms for Mitigating Drought Stress in Crop Plants - Devendra Singh; Shobit Thapa; Jyoti Prakash Singh; Himanshu Mahawar; Anil Kumar Saxena; Sunil Kumar Singh; Hans Raj Mahla; Mahipal Choudhary; Manoj Parihar; Khushwant Babal Choudhary; Hillol Chakdar (Current Microbiology, 2024)

Effect of Excess Fluoride Exposure on Radiographic and Histopathological Changes in Long Bones of Rabbit - Rakesh Ranjan; Devendra Swarup; Anil Kumar Sharma; Hari Prasad Aithal; Amita Ranjan (Biological Trace Element Research, 2024)

Improve the capability of physical model for runoff and sediment yield modelling with a hybrid artificial intelligence-based error updating system - Vijay Kumar Singh; Devendra Kumar; P.S. Kashyap; Sudhir Kumar Singh (Journal of Hydrology, 2024)

Morpho-histological study in the gynodioecious Salvia strobilifera (Lamiaceae) - Pallvi; Gazalpreet Kaur; Kumari Rubal; Devendra Kumar Srivastava; Pradeep Kumar Singh; Amrik Singh Ahluwalia (Vegetos, 2024)

Ultra-low soot/ particulate emissions from a dimethyl ether-fueled agricultural tractor engine - Avinash Kumar Agarwal; Vikram Kumar; Hardikk Valera; Nalini Kanta Mukherjee; Shanti Mehra; Devendra Nene (Fuel, 2024)

Intracellular Iron Accumulation Induces Inflammatory and Oxidative Status of the Host After Japanese Encephalitis Viral Infection - Gajendra Singh; Anjali Singh; Sanjay Mishra; Devendra Singh; Alok Kumar (Molecular Neurobiology, 2024)

Corrigendum to HPTLC quantification of diosgenin in Dioscorea deltoidea: Evaluation of extraction efficacy, organ selection, drying method and seasonal variation South African Journal of Botany Volume 138, May 2021, Pages 386-393 - Romaan Nazir; Vijay Kumar; Abhijit Dey; Devendra Kumar Pandey (South African Journal of Botany, 2023)

Corrigendum to “Screening of elite germplasms for industrially valuable medicinal crop Stevia rebaudiana for stevioside and rebaudioside A production: An HPTLC-linked chemotaxonomic assessment” South African Journal of Botany, volume 150, November 2022, pages 1159-1167 - Shah Nawaz; Prabhjot Kaur; Merinaswari Konjengbam; Vijay Kumar; R.C. Gupta; Padmanabh Dwivedi; Babita Patni; Babita Pandey; Abhijit Dey; Devendra Kumar Pandey (South African Journal of Botany, 2023)

Sub-surface drainage: A win-win technology for achieving carbon neutrality and land amelioration in salt-affected Vertisols of India - Raj Mukhopadhyay; Ram Kishor Fagodiya; Kailash Prajapat; Bhaskar Narjary; Satyendra Kumar; Ranjay K. Singh; Devendra Singh Bundela; Arijit Barman (Geoderma Regional, 2023)

Unveiling novel insights into haloarchaea (Halolamina pelagica CDK2) for alleviation of drought stress in wheat - Devendra Singh; Rajeev Kaushik; Hillol Chakdar; Anil Kumar Saxena (World Journal of Microbiology and Biotechnology, 2023)

RETRACTED ARTICLE: A response surface-based approach to optimize elicitation conditions in Stevia rebaudiana (Bertoni) Bertoni shoot cultures for the enhancement of steviol glycosides - Shah Nawaz; Prabhjot Kaur; Merinaswari Konjengbam; Vijay Kumar; Romaan Nazir; Padmanabh Dwivedi; Tuyelee Das; Abhijit Dey; Devendra Kumar Pandey (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Hsp27 over expression protect against cadmium induced nephrotoxicity in Drosophila melanogaster - Sanjay Saini; Lavi Rani; Neha Shukla; Ravindra Singh Thakur; Devendra Kumar Patel; M.S. Ansari; Monisha Banerjee; Naveen Kumar Gautam (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Nanoarchitectonics of Sulfonated Boron Nitride for Catalytic Synthesis of Aromatic Nitriles under Mild Conditions - Priyanka Choudhary; Shivangi Singh Chauhan; Devendra Sharma; Sahil Kumar; Venkata Krishnan (Chemical Engineering Journal, 2023)

Low expression of lipoxygenase 3 (LOX3) enhances the retention of kernel tocopherols in maize during storage - Shalma Maman; Vignesh Muthusamy; Ashvinkumar Katral; Rashmi Chhabra; Nisrita Gain; Shashidhar Bayappa Reddappa; Suman Dutta; Amolkumar Uddhaorao Solanke; Rajkumar Uttamrao Zunjare; Chirravuri Naga Neeraja; Devendra Kumar Yadava; Firoz Hossain (Molecular Biology Reports, 2023)

A comparative analysis of glacier and glacier-melt runoff changes in western and eastern Himalayan river basins - Vishal Singh; Sanjay Kumar Jain; Devendra Shashikant Nagale (Cold Regions Science and Technology, 2023)

Dyshomeostasis of Iron and Its Transporter Proteins in Cypermethrin-Induced Parkinson’s Disease - Nidhi Sachan; Neha Tiwari; Devendra Kumar Patel; Diksha Katiyar; Saripella Srikrishna; Mahendra Pratap Singh (Molecular Neurobiology, 2023)

Evaluation of uranium content and annual ingestion dose in the surface and ground water bodies of Chittorgarh, Rajasthan, India - Tejpal Menaria; Shailesh Nath Tiwari; Akshay Kumar Patra; Inampudi Vijaya Saradhi; A Vinod Kumar; Rama Kanwar Khangarot; Devendra Singh Rathore (Environmental Monitoring and Assessment, 2023)

An appraisal to hydrochemical characterization, source identification, and potential health risks of sulfate and nitrate in groundwater of Bemetara district, Central India - Mohit Kumar; Mukesh Kumar Sharma; Devendra Singh Malik (Environmental Monitoring and Assessment, 2023)

Restoring soil quality and carbon sequestration potential of waterlogged saline land using subsurface drainage technology to achieve land degradation neutrality in India - Raj Mukhopadhyay; Ram Kishor Fagodiya; Bhaskar Narjary; Arijit Barman; Kailash Prajapat; Satyendra Kumar; Devendra Singh Bundela; Parbodh Chander Sharma (Science of The Total Environment, 2023)

RETRACTED ARTICLE: Role of Polyamines in Molecular Regulation and Cross-Talks Against Drought Tolerance in Plants - Samapika Nandy; Saynati Mandal; Santosh Kumar Gupta; Uttpal Anand; Mimosa Ghorai; Avinash Mundhra; Md. Habibur Rahman; Puja Ray; Sicon Mitra; Durga Ray; Milan Kumar Lal; Rahul Kumar Tiwari; et al. (Journal of Plant Growth Regulation, 2023)

Application of CRISPR/Cas system in optimizing nutrients and anti-nutrients content in fruits - Protha Biswas; Mimosa Ghorai; Samapika Nandy; Potshangbam Nongdam; Devendra Kumar Pandey; Padmanabh Dwivedi; Mahipal S Shekhawat; Abhijit Dey (Vegetos, 2023)

Machine learning based quantification of VOC contribution in surface ozone prediction - Ritesh Kalbande; Bipin Kumar; Sujit Maji; Ravi Yadav; Kaustubh Atey; Devendra Singh Rathore; Gufran Beig (Chemosphere, 2023)

β-triketone herbicide exposure cause tyrosine and fat accumulation in Caenorhabditis elegans - Nida Moin; Ravindra Singh Thakur; Swati Singh; Devendra Kumar Patel; Aruna Satish (Chemosphere, 2023)

Intelligent control of robotic manipulators: a comprehensive review - Devendra Rawat; Mukul Kumar Gupta; Abhinav Sharma (Spatial Information Research, 2023)

Deciphering the mechanisms of microbe mediated drought stress alleviation in wheat - Devendra Singh; Shobit Thapa; Jagriti Yadav; Dikchha Singh; Hillol Chakdar; M. Kumar; Anil Kumar Saxena (Acta Physiologiae Plantarum, 2023)

Diagnostic PCR-based markers for biotic stress resistance breeding in potatoes (Solanum tuberosum L.) - Vikas Mangal; Salej Sood; Vinay Bhardwaj; Vinod Kumar; Ashwani Kumar; Baljeet Singh; Bhawna Dipta; Dalamu Dalamu; Sanjeev Sharma; Ajay Kumar Thakur; Rajender Singh; Ashwani Kumar Sharma; et al. (Australasian Plant Pathology, 2023)

Genetic studies of heat stress regulation in goat during hot climatic condition - Rakesh Kaushik; Aditya Arya; Devendra Kumar; Anjana Goel; P.K. Rout (Journal of Thermal Biology, 2023)

Genome-wide identification and annotation of SNPs and their mapping in candidate genes related to milk production and fertility traits in Badri cattle - Javid Ur Rahman; Devendra Kumar; Satya Pal Singh; Bijendra Narayan Shahi; Ashis Kumar Ghosh; Manish Kumar Verma; Abhishek Pathak; Aashaq Hussain Dar; Anil Kumar; Rabendra Kumar Sharma (Tropical Animal Health and Production, 2023)

A comprehensive and conceptual overview of omics-based approaches for enhancing the resilience of vegetable crops against abiotic stresses - Vikas Mangal; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Ahsan Altaf; Salej Sood; Vijay Gahlaut; Ashish Bhatt; Ajay Kumar Thakur; Ravinder Kumar; Vinay Bhardwaj; Vinod Kumar; Brajesh Singh; et al. (Planta, 2023)

Identification of elite species of Ophiorrhiza utilizing HPTLC analysis and camptothecin as a phytochemical marker: Assessment of extraction effectiveness and organ selection - Merinashwari Konjengbam; Vijay Kumar; Padmanabh Dwivedi; A. Gangaprasad; Abhijit Dey; Devendra Kumar Pandey (Biocatalysis and Agricultural Biotechnology, 2023)

Solar water distillation by wick-type solar stills: a review - Ajay Kumar Sharma; Devendra Singh (Environmental Science and Pollution Research, 2023)

Establishment of direct regeneration protocol for Plumbago auriculata plantlets and comparative HPTLC analysis of plumbagin - Kajal Katoch; Suphla Gupta; Abhijit Dey; Devendra Kumar Pandey (The Nucleus, 2022)

In vitro propagation, genetic and phytochemical fidelity in Glycyrrhiza glabra L., a potent glycyrrhizin yielding endangered plant - Nokcha Wati Ayangla; Padmanabh Dwivedi; Abhijit Dey; Devendra Kumar Pandey (The Nucleus, 2022)

Biotic elicitation for enhanced production of plumbagin in regenerated shoot cultures of Plumbago zeylanica using response surface methodology - Kajal Katoch; Suphla Gupta; Ajai Prakash Gupta; Pooja Goyal; Ritu Devi; Abhijit Dey; Devendra Kumar Pandey (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Chemical characterization of PM10 and PM2.5 combusted firecracker particles during Diwali of Lucknow City, India: air-quality deterioration and health implications - Priya Saxena; Ankit Kumar; SS Kalikinkar Mahanta; Bojjagani Sreekanth; Devendra Kumar Patel; Alka Kumari; Altaf Husain Khan; Ganesh Chandra Kisku (Environmental Science and Pollution Research, 2022)

Centella asiatica Alleviates AlCl3-induced Cognitive Impairment, Oxidative Stress, and Neurodegeneration by Modulating Cholinergic Activity and Oxidative Burden in Rat Brain - Zeba Firdaus; Devendra Kumar; Sushil Kumar Singh; Tryambak Deo Singh (Biological Trace Element Research, 2022)

Combined ligand-based and structure-based design of PDE 9A inhibitors against Alzheimer’s disease - Rayala Swetha; Anjali Sharma; Ravi Singh; Ankit Ganeshpurkar; Devendra Kumar; Ashok Kumar; Sushil K. Singh (Molecular Diversity, 2022)

Targeting the cytochrome bc1 complex for drug development in M. tuberculosis: review - Mushtaq Ahmad Wani; Devendra Kumar Dhaked (Molecular Diversity, 2022)

Modeling the effect of climate change on the distribution of threatened medicinal orchid Satyrium nepalense D. Don in India - Devendra Kumar; Sandeep Rawat (Environmental Science and Pollution Research, 2022)

Predicting the distributional range shifts of Rhizocarpon geographicum (L.) DC. in Indian Himalayan Region under future climate scenarios - Devendra Kumar; Aseesh Pandey; Sandeep Rawat; Mayank Joshi; Rajesh Bajpai; Dalip Kumar Upreti; Surendra Pratap Singh (Environmental Science and Pollution Research, 2022)

Modified DLLME–GC-TQMS determination of pesticide residues in Gomti River, Lucknow, India: ecological risk assessment and multivariate statistical approach - Neha Gupta; Ravindra Singh Thakur; Sandeep Kumar; Gubbala Naga Venkata Satyanarayana; Priyanka Yadav; Swati Tripathi; Nasreen Ghazi Ansari; Devendra Kumar Patel (Environmental Science and Pollution Research, 2022)

Purification and identification of anticancer organosulfides from Ferula assa-foetida gum: integrative analysis employing GC/GC-MS/RP-HPLC/NMR - Priyanka Yatham; Devendra Shukla; Amit K. Srivastava; V.S. Pragadheesh; Deepak Kumar (Natural Product Research, 2022)

Improved machine learning scoring functions for identification of Electrophorus electricus’s acetylcholinesterase inhibitors - Ankit Ganeshpurkar; Ravi Singh; Shalini Shivhare; Divya; Devendra Kumar; Gopichand Gutti; Ravibhushan Singh; Ashok Kumar; Sushil Kumar Singh (Molecular Diversity, 2022)

Beneficial Role of Selenium (Se) Biofortification in Developing Resilience Against Potentially Toxic Metal and Metalloid Stress in Crops: Recent Trends in Genetic Engineering and Omics Approaches - Mimosa Ghorai; Vijay Kumar; Vinay Kumar; Abdel Rahman Al-Tawaha; Mahipal S. Shekhawat; Devendra Kumar Pandey; Gaber El-Saber Batiha; Ercan Bursal; Niraj Kumar Jha; Vijaykumar Shivaji Gadekar; Radha; Manoj Kumar; et al. (Journal of Soil Science and Plant Nutrition, 2022)

Water pollution examination through quality analysis of different rivers: a case study in India - Rohit Sharma; Raghvendra Kumar; Devendra Kumar Sharma; Manash Sarkar; Brojo Kishore Mishra; Vikram Puri; Ishaani Priyadarshini; Pham Huy Thong; Phuong Thao Thi Ngo; Viet-Ha Nhu (Environment, Development and Sustainability, 2022)

Prospecting potential of endophytes for modulation of biosynthesis of therapeutic bioactive secondary metabolites and plant growth promotion of medicinal and aromatic plants - Devendra Singh; Shobit Thapa; Himanshu Mahawar; Dharmendra Kumar; Neelam Geat; S. K. Singh (Antonie van Leeuwenhoek, 2022)

Genetic diversity among local mango (Mangifera indica L.) germplasm using morphological, biochemical and chloroplast DNA barcodes analyses - Sanjay Kumar; Ram Avtar Kaushik; Devendra Jain; Ved Prakash Saini; S. Ramesh Babu; Ravish Choudhary; Sezai Ercisli (Molecular Biology Reports, 2022)

Forest structure and anthropogenic disturbances regulate plant invasion in urban forests - Prakash Chandra Aryal; Chandramani Aryal; Kiran Bhusal; Devendra Chapagain; Man Kumar Dhamala; Sanu Raja Maharjan; Parveen K. Chhetri (Urban Ecosystems, 2022)

Establishment of adventitious root culture from leaf explants of Plumbago zeylanica: an endangered medicinal plant - Kajal Katoch; Suphla Gupta; Romaan Nazir; Vijay Kumar; Rupa Sanyal; Abhijit Dey; Devendra Kumar Pandey (Vegetos, 2022)

Biogenic zinc oxide nanoparticles as an antibacterial, antifungal, and photocatalytic tool mediated via leaves of Girardinia diversifolia - Aayasha Negi; Reena Gangwar; Rahul Kumar Vishwakarma; Devendra Singh Negi (Nanotechnology for Environmental Engineering, 2022)

Studies on Regulation of Global Protein Profile and Cellular Bioenergetics of Differentiating SH-SY5Y Cells - Anuj Pandey; Sana Sarkar; Sanjeev Kumar Yadav; Smriti Singh Yadav; Saripella Srikrishna; Mohammad Haris Siddiqui; Devendra Parmar; Sanjay Yadav (Molecular Neurobiology, 2022)

Identification of Altered Blood MicroRNAs and Plasma Proteins in a Rat Model of Parkinson’s Disease - Sanjeev Kumar Yadav; Anuj Pandey; Sana Sarkar; Smriti Singh Yadav; Devendra Parmar; Sanjay Yadav (Molecular Neurobiology, 2022)

Climate risk insurance in Pacific Small Island Developing States: possibilities, challenges and vulnerabilities—a comprehensive review - Devendra Kumar Jain; Asif Chida; R. D. Pathak; Raghbendra Jha; Stephanie Russell (Mitigation and Adaptation Strategies for Global Change, 2022)

Detection of endophytic association between Aeschynomene nodulating Bradyrhizobium sp. and traditional Desariya rice roots under rice-Aeschynomene ecosystem of chaur land, Bihar, India - Abhilasha Rai; Manindra Nath Jha; Devendra Singh; Shobit Thapa; Sanjeet Kumar Chaurasia; Gopaljee Jha (Biologia Futura, 2022)

Biofortification for high Fe and Zn in various Poaceae crops by using different molecular breeding and biotechnological approaches - Shivangi Negi; Devendra Singh; Himanshu Pandey; Rajesh Kumar Singhal (Plant Physiology Reports, 2021)

Introgression and QTL mapping conferring resistance for Alternaria brassicae in the backcross progeny of Sinapis alba + Brassica juncea somatic hybrids - Kaushal Pratap Singh; Preetesh Kumari; Devendra Kumar Yadava (Plant Cell Reports, 2021)

Evaluation of heavy metal contaminants in prepared noodles: source allocation and health risk assessment - Ravindra Singh Thakur; Aditya Kumar; Onila Lugun; Nasreen Ghazi Ansari; Satgur Prasad; Triparna Das; Neha Gupta; Devendra Kumar Patel (Environmental Science and Pollution Research, 2021)

Plant growth promoting Bacillus-based bio formulations improve wheat rhizosphere biological activity, nutrient uptake and growth of the plant - Priyanka Chandra; Rinki Khobra; Parul Sundha; Rakesh Kumar Sharma; Poonam Jasrotia; Amaresh Chandra; Devendra Pal Singh; Gyanendra Pratap Singh (Acta Physiologiae Plantarum, 2021)

Prospecting catabolic diversity of microbial strains for developing microbial consortia and their synergistic effect on Lentil (Lens esculenta) growth, yield and iron biofortification - Abhinash Kumar; Manindra Nath Jha; Devendra Singh; Devashish Pathak; Mahendra Vikram Singh Rajawat (Archives of Microbiology, 2021)

Effect of microbial consortia on growth and yield of wheat under typic haplustepts - Devendra Jain; Ram Hari Meena; Jagdish Choudhary; Shanti Kumar Sharma; Surya Chauhan; Ali Asger Bhojiya; Sunil Kumar Khandelwal; Santosh Ranjan Mohanty (Plant Physiology Reports, 2021)

Strategies for cryopreservation of testicular cells and tissues in cancer and genetic diseases - Tanushree Patra; Devendra Pathak; Mukesh Kumar Gupta (Cell and Tissue Research, 2021)

Spatio-temporal assessment of ambient air quality, their health effects and improvement during COVID-19 lockdown in one of the most polluted cities of India - Markandeya; Pradeep Kumar Verma; Vibhuti Mishra; Neeraj Kumar Singh; Sheo Prasad Shukla; Devendra Mohan (Environmental Science and Pollution Research, 2021)

Ameliorative role of bosentan, an endothelin receptor antagonist, against sodium arsenite–induced renal dysfunction in rats - Ashwani Kumar Sharma; Japneet Kaur; Tajpreet Kaur; Balbir Singh; Harlokesh Narayan Yadav; Devendra Pathak; Amrit Pal Singh (Environmental Science and Pollution Research, 2021)

Economic and environmental impact analyses of hybrid generation system in respect to Rajasthan - Amit Shrivastava; Devendra Kumar Doda; Mahesh Bundele (Environmental Science and Pollution Research, 2021)

Correction to: Influence of Exogenous Silicon Addition on Aluminium Tolerance in Rice Seedlings - Vijay Pratap Singh; Durgesh Kumar Tripathi; Dharmendra Kumar; Devendra Kumar Chauhan (Biological Trace Element Research, 2021)

Plant Natural Products as Neuroprotective Nutraceuticals: Preclinical and Clinical Studies and Future Implications - Abhijit Dey; Samapika Nandy; Anuradha Mukherjee; Devendra Kumar Pandey (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

In vitro evaluation to intensify the differential morphogenetic response through plant growth regulators and antibiotic supplementation in sugarcane - Devendra Kumar; Rakesh Singh Sengar; Nisha Malik; Manoj Kumar Yadav; Shalani Gupta; Pooran Chand; Gopal Singh; Pushpendra Kumar (Plant Physiology Reports, 2020)

Spatial distribution and identification of bacteria in stressed environments capable to weather potassium aluminosilicate mineral - Mahendra Vikram Singh Rajawat; Rajni Singh; Devendra Singh; Ajar Nath Yadav; Surender Singh; Murugan Kumar; Anil Kumar Saxena (Brazilian Journal of Microbiology, 2020)

Synergistic inoculation of Azotobacter vinelandii and Serendipita indica augmented rice growth - Surbhi Dabral; Saurabh C. Saxena; Devendra Kumar Choudhary; Prasun Bandyopadhyay; Ranjan Kumar Sahoo; Narendra Tuteja; Manoj Nath (Symbiosis, 2020)

Postnatal zinc or paraquat administration increases paraquat or zinc-induced loss of dopaminergic neurons: insight into augmented neurodegeneration - Namrata Mittra; Amit Kumar Chauhan; Garima Singh; Devendra Kumar Patel; Chetna Singh (Molecular and Cellular Biochemistry, 2020)

Analysis of genetic divergence and population structure through microsatellite markers in normal and quality protein maize genotypes from NW Himalayan region of India - Nisha Malik; Devendra Kumar; B. Kalyana Babu (Vegetos, 2020)

Silymarin Protects Against Impaired Autophagy Associated with 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine-Induced Parkinsonism - Manish Kumar Tripathi; Mohd Sami Ur Rasheed; Abhishek Kumar Mishra; Devendra Kumar Patel; Mahendra Pratap Singh (Journal of Molecular Neuroscience, 2020)

Performance of low and high Fe accumulator wheat genotypes grown on soils with low or high available Fe and endophyte inoculation - Devendra Singh; Neelam Geat; Mahendra Vikram Singh Rajawat; Radha Prasanna; Anil Kumar Saxena (Acta Physiologiae Plantarum, 2020)

Interactive Effect of Silicon (Si) and Salicylic Acid (SA) in Maize Seedlings and Their Mechanisms of Cadmium (Cd) Toxicity Alleviation - Swati Singh; Vijay Pratap Singh; Sheo Mohan Prasad; Shivesh Sharma; Naleeni Ramawat; Nawal Kishore Dubey; Durgesh Kumar Tripathi; Devendra Kumar Chauhan (Journal of Plant Growth Regulation, 2019)

Inferring air pollution from air quality index by different geographical areas: case study in India - Rohit Sharma; Raghvendra Kumar; Devendra Kumar Sharma; Le Hoang Son; Ishaani Priyadarshini; Binh Thai Pham; Dieu Tien Bui; Sakshi Rai (Air Quality, Atmosphere & Health, 2019)

Correction to: Prenatal Exposure of Cypermethrin Induces Similar Alterations in Xenobiotic-Metabolizing Cytochrome P450s and Rate-Limiting Enzymes of Neurotransmitter Synthesis in Brain Regions of Rat Offsprings During Postnatal Development - Anshuman Singh; Anubha Mudawal; Pratibha Maurya; Rajeev Jain; Saumya Nair; Rajendra K. Shukla; Sanjay Yadav; Dhirendra Singh; Vinay Kumar Khanna; Rajnish Kumar Chaturvedi; Mohana K. R. Mudiam; Rao Sethumadhavan; et al. (Molecular Neurobiology, 2019)

Correction to: CYP2E1-mediated oxidative stress regulates HO-1 and GST expression in maneb- and paraquat-treated rat polymorphonuclear leukocytes - Israr Ahmad; Smriti Shukla; Deepali Singh; Amit Kumar Chauhan; Vinod Kumar; Brajesh Kumar Singh; Devendra Kumar Patel; Haushila Prasad Pandey; Chetna Singh (Molecular and Cellular Biochemistry, 2019)

Understanding Heavy Metal Stress in a Rice Crop: Toxicity, Tolerance Mechanisms, and Amelioration Strategies - Namira Arif; Nilesh C. Sharma; Vaishali Yadav; Naleeni Ramawat; Nawal Kishore Dubey; Durgesh Kumar Tripathi; Devendra Kumar Chauhan; Shivendra Sahi (Journal of Plant Biology, 2019)

Endophytic Bacteria in Plant Salt Stress Tolerance: Current and Future Prospects - Anukool Vaishnav; Awadhesh K. Shukla; Anjney Sharma; Roshan Kumar; Devendra K. Choudhary (Journal of Plant Growth Regulation, 2019)

Retraction Note to: Ecological Significance of Microdiversity: Coexistence Among Casing Soil Bacterial Strains Through Allocation of Nutritional Resource - Devendra Kumar Choudhary; Bhavdish N. Johri (Indian Journal of Microbiology, 2019)

Comparative analysis for understanding salinity tolerance mechanism in Indian Mustard (Brassica juncea L.) - Binay K. Singh; Surendra P. Singh; Kapila Shekhawat; Sanjay S. Rathore; Avinash Pandey; Sudhir Kumar; Devendra K. Singh; Shashi Bhushan Choudhry; Saurav Kumar; Dhiraj Singh (Acta Physiologiae Plantarum, 2019)

Effect of Gender, Age, Diet and Smoking Status on the Circadian Rhythm of Serum Uric Acid of Healthy Indians of Different Age Groups - Ranjana Singh; Pramod Kumar; Devendra Nath Mishra; Ashok Kumar Singh; Raj Kumar Singh; Abbas Ali Mahdi; Cathy Lee Gierke; Germaine Cornelissen (Indian Journal of Clinical Biochemistry, 2019)

Regulation of Drought-Responsive Gene Expression in Glycine max L. Merrill is Mediated Through Pseudomonas simiae Strain AU - Anukool Vaishnav; Devendra Kumar Choudhary (Journal of Plant Growth Regulation, 2019)

Calibration and validation of SWAT model using stream flow and sediment load for Mojo watershed, Ethiopia - Zelalem Biru; Devendra Kumar (Sustainable Water Resources Management, 2018)

The role of T regulatory cell-associated markers in monitoring tuberculosis treatment completion and failure - Sonali Agrawal; Om Parkash; Alangudi Natarajan Palaniappan; Ashok K. Bhatia; Santosh Kumar; Devendra S. Chauhan; M. Madhan Kumar (Immunologic Research, 2018)

Understanding genetic relationship and population structure of Indian soybean varieties using microsatellite markers - Devendra Kumar Chauhan; Javaid Akhter Bhat; Ajay Kumar Thakur; Zakir Hussain; C. Tara Satyavathi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Characterization and Identification of Recalcitrant Organic Pollutants (ROPs) in Tannery Wastewater and Its Phytotoxicity Evaluation for Environmental Safety - Ram Naresh Bharagava; Gaurav Saxena; Sikandar I. Mulla; Devendra Kumar Patel (Archives of Environmental Contamination and Toxicology, 2018)

Alpha-synuclein aggregation, Ubiquitin proteasome system impairment, and l-Dopa response in zinc-induced Parkinsonism: resemblance to sporadic Parkinson’s disease - Vinod Kumar; Deepali Singh; Brajesh Kumar Singh; Shweta Singh; Namrata Mittra; Rakesh Roshan Jha; Devendra Kumar Patel; Chetna Singh (Molecular and Cellular Biochemistry, 2018)

Identification of Ideal Locations and Stable High Biomass Sorghum Genotypes in semiarid Tropics - G. S. Anil Kumar; K. S. Vinutha; Devendra Kumar Shrivastava; S. Jain; B. A. Syed; B. Gami; S. Marimuthu; A. Yuvraj; H. S. Yadava; S. C. Srivastava; K. Yadagiri; V. Ansodariya; et al. (Sugar Tech, 2018)

Biotechnological aspects of the production of natural sweetener glycyrrhizin from Glycyrrhiza sp. - Devendra Kumar Pandey; N. W. Ayangla (Phytochemistry Reviews, 2018)

Ibuprofen Protects from Cypermethrin-Induced Changes in the Striatal Dendritic Length and Spine Density - Pratibha Tripathi; Ashish Singh; Lakshmi Bala; Devendra Kumar Patel; Mahendra Pratap Singh (Molecular Neurobiology, 2018)

Cyclooxygenase-2 Directs Microglial Activation-Mediated Inflammation and Oxidative Stress Leading to Intrinsic Apoptosis in Zn-Induced Parkinsonism - Amit Kumar Chauhan; Namrata Mittra; Devendra Kumar Patel; Chetna Singh (Molecular Neurobiology, 2018)

Deciphering the Mechanisms of Endophyte-Mediated Biofortification of Fe and Zn in Wheat - Devendra Singh; Neelam Geat; Mahendra Vikram Singh Rajawat; Mahesh M. Mahajan; Radha Prasanna; Surender Singh; Rajeev Kaushik; Ram Nageena Singh; Kanika Kumar; Anil Kumar Saxena (Journal of Plant Growth Regulation, 2018)

Cypermethrin Activates Autophagosome Formation Albeit Inhibits Autophagy Owing to Poor Lysosome Quality: Relevance to Parkinson’s Disease - Abhishek Kumar Mishra; Saumya Mishra; Charul Rajput; Mohd Sami ur Rasheed; Devendra Kumar Patel; Mahendra Pratap Singh (Neurotoxicity Research, 2018)

Design, synthesis, characterization, and molecular modeling studies of novel oxadiazole derivatives of nipecotic acid as potential anticonvulsant and antidepressant agents - Ravi Bhushan Singh; Gireesh Kumar Singh; Krishna Chaturvedi; Devendra Kumar; Sushil Kumar Singh; Md. Kamaruz Zaman (Medicinal Chemistry Research, 2018)

Isolation and Characterization of Phosphate Solubilizing Bacteria from Rhizosphere of Dioscorea alata Stimulating Growth and Diosgenin Production - Devendra Kumar Pandey; Adil Nazir; Abhijit Dey (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Camel Milk: An Important Natural Adjuvant - Raghvendar Singh; Gorakh Mal; Devendra Kumar; N. V. Patil; K. M. L. Pathak (Agricultural Research, 2017)

Quality, functionality, and shelf life of fermented meat and meat products: A review - Pavan Kumar; M. K. Chatli; Akhilesh K. Verma; Nitin Mehta; O. P. Malav; Devendra Kumar; Neelesh Sharma (Critical Reviews in Food Science and Nutrition, 2017)

Differentiation Induces Dramatic Changes in miRNA Profile, Where Loss of Dicer Diverts Differentiating SH-SY5Y Cells Toward Senescence - Abhishek Jauhari; Tanisha Singh; Ankita Pandey; Parul Singh; Nishant Singh; Ankur Kumar Srivastava; Aditya Bhushan Pant; Devendra Parmar; Sanjay Yadav (Molecular Neurobiology, 2017)

Beneficial role of endophytes in biofortification of Zn in wheat genotypes varying in nutrient use efficiency grown in soils sufficient and deficient in Zn - Devendra Singh; Mahendra Vikram Singh Rajawat; Rajeev Kaushik; Radha Prasanna; Anil Kumar Saxena (Plant and Soil, 2017)

Neuronal Nitric Oxide Synthase Negatively Regulates Zinc-Induced Nigrostriatal Dopaminergic Neurodegeneration - Brajesh Kumar Singh; Vinod Kumar; Amit Kumar Chauhan; Ashish Dwivedi; Shweta Singh; Ashutosh Kumar; Deepali Singh; Devendra Kumar Patel; Ratan Singh Ray; Swatantra Kumar Jain; Chetna Singh (Molecular Neurobiology, 2017)

Chitinolytic Bacillus-Mediated Induction of Jasmonic Acid and Defense-Related Proteins in Soybean (Glycine max L. Merrill) Plant Against Rhizoctonia solani and Fusarium oxysporum - Shekhar Jain; Anukool Vaishnav; Sarita Kumari; Ajit Varma; Narendra Tuteja; Devendra Kumar Choudhary (Journal of Plant Growth Regulation, 2017)

Inflammation and B-cell Lymphoma-2 Associated X Protein Regulate Zinc-Induced Apoptotic Degeneration of Rat Nigrostriatal Dopaminergic Neurons - Amit Kumar Chauhan; Namrata Mittra; Vinod Kumar; Devendra Kumar Patel; Chetna Singh (Molecular Neurobiology, 2016)

Prenatal Exposure of Cypermethrin Induces Similar Alterations in Xenobiotic-Metabolizing Cytochrome P450s and Rate-Limiting Enzymes of Neurotransmitter Synthesis in Brain Regions of Rat Offsprings During Postnatal Development - Anshuman Singh; Anubha Mudawal; Pratibha Maurya; Rajeev Jain; Saumya Nair; Rajendra K. Shukla; Sanjay Yadav; Dhirendra Singh; Vinay Kumar Khanna; Rajnish Kumar Chaturvedi; Mohana K. R. Mudiam; Rao Sethumadhavan; et al. (Molecular Neurobiology, 2016)

Minocycline Rescues from Zinc-Induced Nigrostriatal Dopaminergic Neurodegeneration: Biochemical and Molecular Interventions - Vinod Kumar; Brajesh Kumar Singh; Amit Kumar Chauhan; Deepali Singh; Devendra Kumar Patel; Chetna Singh (Molecular Neurobiology, 2016)

Design and development of pyrrole carbaldehyde: an effective pharmacophore for enoyl-ACP reductase - Shrinivas D. Joshi; Devendra Kumar; Uttam A. More; Kap Seung Yang; Tejraj M. Aminabhavi (Medicinal Chemistry Research, 2016)

Otolith fingerprints reveal stock discrimination of Sperata seenghala inhabiting the Gangetic river system - Kaish Miyan; Mohammad Afzal Khan; Devendra Kumar Patel; Shahista Khan; Satgur Prasad (Ichthyological Research, 2016)

Induced Inorganic Phosphate Solubilization Through N-Methyl-N´-Nitro-N-Nitrosoguanidine Treated Mutants of Pseudomonas koreensis Strain AK-1 (MTCC Number 12058) Under Polyethylene Glycol - Amrita Kasotia; Devendra Kumar Choudhary (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Bacterial-Mediated Tolerance and Resistance to Plants Under Abiotic and Biotic Stresses - Devendra Kumar Choudhary; Amrita Kasotia; Shekhar Jain; Anukool Vaishnav; Sarita Kumari; Kanti Prakash Sharma; Ajit Varma (Journal of Plant Growth Regulation, 2016)

Dual symbiosis between Piriformospora indica and Azotobacter chroococcum enhances the artemisinin content in Artemisia annua L. - Monika Arora; Parul Saxena; Devendra Kumar Choudhary; Malik Zainul Abdin; Ajit Varma (World Journal of Microbiology and Biotechnology, 2016)

Induced drought tolerance through wild and mutant bacterial strain Pseudomonas simiae in mung bean (Vigna radiata L.) - Sarita Kumari; Anukool Vaishnav; Shekhar Jain; Ajit Varma; Devendra Kumar Choudhary (World Journal of Microbiology and Biotechnology, 2016)

Metabolomic Analysis Provides Insights on Paraquat-Induced Parkinson-Like Symptoms in Drosophila melanogaster - Arvind Kumar Shukla; Ch. Ratnasekhar; Prakash Pragya; Hitesh Singh Chaouhan; Devendra Kumar Patel; Debapratim Kar Chowdhuri; Mohana Krishna Reddy Mudiam (Molecular Neurobiology, 2016)

Cyclosporine A and MnTMPyP Alleviate α-Synuclein Expression and Aggregation in Cypermethrin-Induced Parkinsonism - Sonal Agrawal; Anubhuti Dixit; Ashish Singh; Pratibha Tripathi; Dhirendra Singh; Devendra Kumar Patel; Mahendra Pratap Singh (Molecular Neurobiology, 2015)

Bacterial-Mediated Induction of Systemic Tolerance to Salinity with Expression of Stress Alleviating Enzymes in Soybean (Glycine max L. Merrill) - Sarita Kumari; Anukool Vaishnav; Shekhar Jain; Ajit Varma; Devendra Kumar Choudhary (Journal of Plant Growth Regulation, 2015)

An ecological role of fungal endophytes to ameliorate plants under biotic stress - Neha Chadha; Manjita Mishra; Kartikeya Rajpal; Ruchika Bajaj; Devendra Kumar Choudhary; Ajit Varma (Archives of Microbiology, 2015)

Pseudomonas-Mediated Mitigation of Salt Stress and Growth Promotion in Glycine max - Amrita Kasotia; Ajit Varma; Devendra Kumar Choudhary (Agricultural Research, 2015)

Prevalence of Pathological Conditions in Zoo/Wild Animals in India: A Retrospective Study Based on Necropsy - Anil Kumar Sharma; Shivasharanappa Nayakwadi; Gauri Arvind Chandratre; Mohini Saini; Asit Das; Sachin Shaligram Raut; Devendra Swarup; Ramesh Somvanshi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

RNAi mediated gene silencing against betasatellite associated with Croton yellow vein mosaic begomovirus - Anurag Kumar Sahu; Avinash Marwal; Chitra Nehra; Devendra Kumar Choudhary; Pradeep Sharma; Rajarshi Kumar Gaur (Molecular Biology Reports, 2014)

Docking, CoMFA, and CoMSIA analyses of phenoxy triazole derivatives as enoyl-ACP reductase inhibitors for Escherichia coli - Shrinivas D. Joshi; Devendra Kumar; Uttam A. More; Tejraj M. Aminabhavi (Medicinal Chemistry Research, 2014)

CYP2E1-mediated oxidative stress regulates HO-1 and GST expression in maneb- and paraquat-treated rat polymorphonuclear leukocytes - Israr Ahmad; Smriti Shukla; Deepali Singh; Amit Kumar Chauhan; Vinod Kumar; Brajesh Kumar Singh; Devendra Kumar Patel; Haushila Prasad Pandey; Chetna Singh (Molecular and Cellular Biochemistry, 2014)

Induced defense-related proteins in soybean (Glycine max L. Merrill) plants by Carnobacterium sp. SJ-5 upon challenge inoculation of Fusarium oxysporum - Shekhar Jain; Devendra Kumar Choudhary (Planta, 2014)

Effect of treatment of cow’s urine “Gomutra” and antioxidants in alleviating the lindane-induced oxidative stress in kidney of Swiss mice (Mus musculus) - Girima Nagda; Devendra Kumar Bhatt (Molecular Biology Reports, 2014)

Rhizobacterium-mediated growth promotion and expression of stress enzymes in Glycine max L. Merrill against Fusarium wilt upon challenge inoculation - Shekhar Jain; Anukool Vaishnav; Amrita Kasotia; Sarita Kumari; Rajarshi Kumar Gaur; Devendra Kumar Choudhary (World Journal of Microbiology and Biotechnology, 2014)

Phytoremediation Potential and Nutrient Status of Barringtonia acutangula Gaerth. Tree Seedlings Grown Under Different Chromium (CrVI) Treatments - Dharmendra Kumar; Durgesh Kumar Tripathi; Devendra Kumar Chauhan (Biological Trace Element Research, 2014)

Bacteria-induced systemic resistance and growth promotion in Glycine max L. Merrill upon challenge inoculation with Fusarium oxysporum - Shekhar Jain; Anukool Vaishnav; Amrita Kasotia; Sarita Kumari; Rajarshi Kumar Gaur; Devendra Kumar Choudhary (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Comprehensive screening of heterocyclic compound libraries to identify novel inhibitors for PfRIO-2 kinase through docking and substrate competition studies - Swagata Nag; Devendra Kumar Chouhan; S. N. Balaji; Arnish Chakraborty; Kimjolly Lhouvum; Chandralata Bal; Ashoke Sharon; Vishal Trivedi (Medicinal Chemistry Research, 2013)

Differential responses of antioxidant system and photosynthetic characteristics in four rice cultivars differing in sensitivity to sodium chloride stress - Ramani Kumar Sarkar; Kanti Ranjan Mahata; Devendra Pratap Singh (Acta Physiologiae Plantarum, 2013)

Comparative palynological and wood anatomical studies of Indian Taxus wallichiana Zucc., Cephalotaxus mannii Hook. and Cephalotaxus griffithii Hook. - Deepika Yadav; Pradeep Kumar; Satyendra Prakash Tiwari; Devendra Kumar Chauhan (Plant Systematics and Evolution, 2013)

Imprinting of Cerebral and Hepatic Cytochrome P450s in Rat Offsprings Exposed Prenatally to Low Doses of Cypermethrin - Anshuman Singh; Sanjay Yadav; Vikas Srivastava; Rakesh Kumar; Dhirendra Singh; Rao Sethumadhavan; Devendra Parmar (Molecular Neurobiology, 2013)

Complete nucleotide sequence of a begomovirus associated with satellites molecules infecting a new host Tagetes patula in India - Avinash Marwal; Anurag Kumar Sahu; Devendra Kumar Choudhary; R. K. Gaur (Virus Genes, 2013)

Effect of nitric oxide signaling in bacterial-treated soybean plant under salt stress - Anukool Vaishnav; Shekhar Jain; Amrita Kasotia; Sarita Kumari; Rajarshi Kumar Gaur; Devendra Kumar Choudhary (Archives of Microbiology, 2013)

Typological and Frequency Based Study of Opaline Silica (Phytolith) Deposition in Two Common Indian Sorghum L. Species - Durgesh Kumar Tripathi; Sanjay Mishra; Devendra Kumar Chauhan; Satyendra Prakash Tiwari; Chitranjan Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

A condensed phenylpropanoid glucoside and pregnane saponins from the roots of Hemidesmus indicus - Zhimin Zhao; Katsuyoshi Matsunami; Hideaki Otsuka; Nisha Negi; Ashok Kumar; Devendra Singh Negi (Journal of Natural Medicines, 2013)

Laser-Induced Breakdown Spectroscopy and Phytolith Analysis: An Approach to Study the Deposition and Distribution Pattern of Silicon in Different Parts of Wheat (Triticum aestivum L.) Plant - Durgesh Kumar Tripathi; Rohit Kumar; Ashok Kumar Pathak; Devendra Kumar Chauhan; Awadhesh Kumar Rai (Agricultural Research, 2012)

Psoroptes cuniculi induced oxidative imbalance in rabbits and its alleviation by using vitamins A, D3, E, and H as adjunctive remedial - Shanker Kumar Singh; Umesh Dimri; Mahesh Chandra Sharma; Devendra Swarup; Mritunjay Kumar; Ramesh Tiwary (Tropical Animal Health and Production, 2012)

Impact of exogenous silicon addition on chromium uptake, growth, mineral elements, oxidative stress, antioxidant capacity, and leaf and root structures in rice seedlings exposed to hexavalent chromium - Durgesh Kumar Tripathi; Vijay Pratap Singh; Dharmendra Kumar; Devendra Kumar Chauhan (Acta Physiologiae Plantarum, 2012)

Influence of Exogenous Silicon Addition on Aluminium Tolerance in Rice Seedlings - Vijay Pratap Singh; Durgesh Kumar Tripathi; Dharmendra Kumar; Devendra Kumar Chauhan (Biological Trace Element Research, 2011)

Phytochemical investigation and antifeedant activity of Premna latifolia leaves - Ashok Kumar; Mahendra Lal Tamta; Nisha Negi; K. Chandrasekhar; Devendra Singh Negi (Natural Product Research, 2011)

Bioassay as monitoring system for lead phytoremediation through Crinum asiaticum L. - Mayank Varun; Rohan D’Souza; Devendra Kumar; Manoj S. Paul (Environmental Monitoring and Assessment, 2011)

Anti-biofilm potential of a glycolipid surfactant produced by a tropical marine strain of Serratia marcescens - Devendra H. Dusane; Vinay S. Pawar; Y. V. Nancharaiah; V. P. Venugopalan; Ameeta Ravi Kumar; Smita S. Zinjarde (Biofouling, 2011)

Cross-Species Induction of Antimicrobial Compounds, Biosurfactants and Quorum-Sensing Inhibitors in Tropical Marine Epibiotic Bacteria by Pathogens and Biofouling Microorganisms - Devendra H. Dusane; Pratiek Matkar; Valayam P. Venugopalan; Ameeta Ravi Kumar; Smita S. Zinjarde (Current Microbiology, 2011)

RETRACTED ARTICLE: Ecological Significance of Microdiversity: Coexistence Among Casing Soil Bacterial Strains Through Allocation of Nutritional Resource - Devendra Kumar Choudhary; Bhavdish N. Johri (Indian Journal of Microbiology, 2011)

Indoor exposure to respirable particulate matter and particulate-phase PAHs in rural homes in North India - Furquan Ahmad Ansari; Altaf Husain Khan; Devendra Kumar Patel; Huma Siddiqui; Shachi Sharma; Mohammad Ashquin; Iqbal Ahmad (Environmental Monitoring and Assessment, 2010)

Isolation of pyrene degrading Achromobacter xylooxidans and characterization of metabolic product - Jitendra Nath Tiwari; Mudiam Mohana Krishna Reddy; Devendra Kumar Patel; Sudhir Kumar Jain; Ramesh Chandra Murthy; Natesan Manickam (World Journal of Microbiology and Biotechnology, 2010)

Occurrence of phthalic acid esters in Gomti River Sediment, India - Abhinav Srivastava; Vinod P. Sharma; Ranu Tripathi; Rakesh Kumar; Devendra K. Patel; Pradeep Kumar Mathur (Environmental Monitoring and Assessment, 2010)

Identification of polycyclic aromatic hydrocarbons in unleaded petrol and diesel exhaust emission - Vinay Kumar Yadav; Sahdeo Prasad; Devendra K. Patel; Altaf Husain Khan; Madhu Tripathi; Yogeshwer Shukla (Environmental Monitoring and Assessment, 2010)

Evaluation of in situ functional activity of casing soils during growth cycle of mushroom (Agaricus bisporus (Lange) Imbach) employing community level physiological profiles (CLPPs) - Devendra Kumar Choudhary; Pavan K. Agarwal; Bhavdish N. Johri (Indian Journal of Microbiology, 2010)

Distribution, Sources and Characterization of Polycyclic Aromatic Hydrocarbons in the Sediment of the River Gomti, Lucknow, India - Ranu Tripathi; Rakesh Kumar; Mohan Krishna Reddy Mudiam; Devendra K. Patel; Jai Raj Behari (Bulletin of Environmental Contamination and Toxicology, 2009)

Reduction of pollutants in pulp paper mill effluent treated by PCP-degrading bacterial strains - Ram Chandra; Abhay Raj; Sangeeta Yadav; Devendra Kumar Patel (Environmental Monitoring and Assessment, 2009)

Cartap and carbofuran induced alterations in serum lipid profile of Wistar rats - Devendra K. Rai; Prashant Kumar Rai; Aradhna Gupta; Geeta Watal; Bechan Sharma (Indian Journal of Clinical Biochemistry, 2009)

Effect of water extract of Trichosanthes dioica fruits in streptozotocin induced diabetic rats - Prashant Kumar Rai; Dolly Jaiswal; Devendra K. Rai; Bechan Sharma; Geeta Watal (Indian Journal of Clinical Biochemistry, 2008)

Molecular Analysis of Soybean Cultivars Differing in Response to Salinity Stress - R. K. Singh; Anita Rani; Devendra K. Chauhan; K. V. Bhat; V. Kumar; C. Tara Satyavathi; S. M. Husain (Journal of Plant Biochemistry and Biotechnology, 2008)

Molecular characterization of coding sequences and analysis of Toll-like receptor 3 mRNA expression in water buffalo (Bubalus bubalis) and nilgai (Boselaphus tragocamelus) - Animesh Dhara; Mohini Saini; Dhanjit K. Das; Devendra Swarup; Bhaskar Sharma; Satish Kumar; Praveen K. Gupta (Immunogenetics, 2006)

Removal of peroxides in polyethylene glycols by vacuum drying: Implications in the stability of biotech and pharmaceutical formulations - Vineet Kumar; Devendra S. Kalonia (AAPS PharmSciTech, 2006)